Linguoculturological Approach in the Study of Languages - Nazarova Manzura (Peerian Journals Publishing, 2022)
The article considers a new approach, which is permissible when studying Russian as a foreign language. The linguoculturological approach to language learning is more effective in the educational process
Keywords: process; learning; approach